Hierarchy, Ability, and Income Distribution - Calvo, Guillermo A.; Wellisz, Stanislaw (Journal of Political Economy, 1979)
Labor allocation and wage-scale formation are studied in the context of competitive hierarchic firms. We show that (1) the wage per effective laborer and his quality increase with the hierarchical position of the employee, and (2) up to a point, the imposition of a minimum wage for production labor increases the quality and quantity of production workers and reduces the wage, quality, and number of supervisors. These results help to explain the skewness of income distribution, and the wage differentials across layers which are inexplicable in terms of differences in labor quality and difficulty of tasks.